TRANSFORMATIONAL LEADERSHIP AND ITS INFLUENCE ON EMPLOYEE INNOVATION IN TECH COMPANIES - Paspa Granita; Oktavianti; Rizki Eka Putra (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
In the hyper-competitive technology sector, innovation is a imperative for survival, yet many companies struggle to cultivate it. This study investigates the critical role of transformational leadership as a catalyst for employee-driven innovation. Through an empirical analysis of tech professionals, the research demonstrates that transformational leadership significantly predicts innovative work behavior. The findings reveal a nuanced mechanism: the leadership components exert distinct, stage-specific influences. Intellectual Stimulation is the primary driver of idea generation, while Inspirational Motivation and Individualized Consideration fuel idea promotion and realization by fostering intrinsic motivation and psychological safety. This study provides a validated "Leadership-Innovation Nexus" model, confirming that leadership behaviors directly create the psychological environment essential for innovation. The results offer a clear blueprint for tech companies, highlighting that developing transformational leaders is not a soft skill but a strategic necessity to systematically unlock innovative potential and secure a competitive advantage.